Synthesis and Characterization of Composite Materials Based on Bacterial Cellulose and Fly Ash - Yuliah, Maya; Sutanto, Teja Dwi; Maryanti, Evi; Angasa, Eka; Gustian, Irfan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The synthesis of composite materials based on bacterial cellulose with fly ash (FA) has been carried out based on the mass ratio between bacterial cellulose and fly ash, namely 0.005:4.995; 0.01:4.99; 0.015:4.985, and 0.02:4.98. Bacterial cellulose was obtained from the fermentation of coconut water and fly ash was treated after being obtained from the Steam Power Plant (PLTU) of Bengkulu Electric Power Plant Pulau Baai. The characterization of the composite material that had been formed was analyzed using Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Raman Spectroscopy, and Scanning Electron Microscope (SEM), the results can be validated that the bacterial cellulose composite has been formed with fly ash. The FTIR results also support the XRD results that have been obtained, Raman spectroscopy shows a Raman shift at 1352 cm-1 as an indication of the bending of C-C-H, CH2, and C-OH the highest conductivity was obtained in the variation of 0.02:4.98 which is 2.45×10-3 S/cm. The methanol permeability test obtained was higher along with the addition of fly ash to bacterial cellulose occurred in the composite material variation of 0.02:4.98, which is 3.66×10-9 mol/cm.s. The highest water absorption occurred in the composite material variation of 0.01:4.98 reaching 718% and the results of SEM micrographs with a magnification of 10000× produced a morphology in the form of fibers with fly ash components interwoven by bacterial cellulose fibers.